Tahajjud Prayer and Its Association with Anthropometric and Blood Pressure Parameters in Young Adults: A Cross-Sectional Study - Yusni, Yusni; Rahman, Safrizal (Department of Nursing, Faculty of Medicine, Universitas Diponegoro, 2025)
Background: The spiritual significance of Tahajjud (Islamic voluntary night prayer) is well established; however, its association with physiological markers, such as body weight (BW), body mass index (BMI), and blood pressure (BP), particularly in relation to gender, remains underexplored.Purpose: This study aimed to assess the association between Tahajjud prayer and anthropometric and BP parameters in young adults by comparing Tahajjud and non-Tahajjud groups, as well as regular and irregular Tahajjud practice, with attention to gender differences.Methods: A cross-sectional study was conducted among 462 Muslim participants (206 men, 256 women) aged 18–22 years. Data on demographics, religious practices, and Tahajjud frequency were collected through questionnaires. Participants were categorized into Tahajjud and non-Tahajjud groups; those who performed Tahajjud were further classified as regular (≥3 times/week) or irregular (<3 times/week). BP was measured using a digital sphygmomanometer, BW with a digital scale, and height with a digital stadiometer. Comparisons of BW, BMI, and BP were made across Tahajjud and non-Tahajjud groups, regular and irregular Tahajjud practitioners, and by gender. Data were analyzed using Chi-square and t-tests at a 95% confidence level (p<0.05).Results: The prevalence of Tahajjud practice was higher among women than men, both overall (70.71% vs. 66.51%) and for regular practice (32.04% vs. 13.86%), with a significant gender difference in regular Tahajjud (p=0.001). No significant gender-specific differences in BW or BMI were observed between Tahajjud and non-Tahajjud groups. Among women, systolic BP was significantly lower in the Tahajjud group (p=0.001). Regular Tahajjud practice was associated with lower BW and BMI in both women (p<0.005) and men (p<0.05). Although systolic and diastolic BP were lower among regular Tahajjud practitioners, differences were not statistically significant. Irregular Tahajjud was associated with a higher prevalence of overweight and obesity (p=0.016).Conclusions: Regular Tahajjud practice was associated with lower BW, BMI, and modest reductions in BP, suggesting a potential role in obesity prevention and cardiovascular health. Nurses can incorporate culturally relevant practices, such as Tahajjud, into health education and lifestyle counseling programs.